The Influence of Green Accounting, Environmental Performance, and Environmental Disclosure on Financial Performance - Agusta, Tony (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of green accounting, environmental performance, and environmental disclosure on financial performance. This study uses a purposive sampling method, which is a technique for selecting samples as data sources based on specific considerations or reasons. Secondary data was obtained from the website www.idx.com. The population used was mining companies registered in 2018 and 2022. Of these criteria, 25 companies met the sample criteria. Data were analyzed using the inner method and hypothesis testing. The results of the study indicate a positive and significant influence of green accounting, environmental performance, and environmental disclosure on financial performance.